Importância de diferentes microhabitats no comportamento de forrageio por presas do mico-leão-preto, Leontopithecus chrysopygus (Mikan) (Mammalia, Callitrichidae) - Passos, Fernando C. (2001)
Prey foraging behavior in the Black Lion Tamarin, Leonlopilhecus cllIysopygus (Mikan, 1823) was observed in the Caetetus Ecological Station, southeastern Brazil , during 550 hours of direct observations between December 1993 and FebrualY 1995. The scan sampling method was used to gather data. These tamarins use manipulative, specific-si te foraging behavior. When searching for animal prey items, they examine a variety of microhabitats. The most important microhabitat used for prey foraging behavior was tree caviti es (41 % of the foraging observat ions), but paim trees (22%), bamboo ( 12%), vines (11 %), bark (5%), seed pods of the 'jequitiba" lree (4%), olher places (3%) and epiphyles (2%) were also observed. Animal preys were fi'equenl ly captured in understOlY (7 1.6%, n = 96) and in middle layers (2 1.6%, n = 29), but infi'equently in the canopy (5.9%, n = 8) and in the ground (0.7%, n = I). Prey foraging behavior showed a similar pattern to that observed for animal prey caplured: 54.9% (n = 380) in underslory, 35.5% (n = 246) in middle layers, 8.9% (n = 62) in lhe canopy and 0.6% (n = 4) in the ground. Thus, the understory and middle layers are lhe mos! important foraging areas. Also, apparently only L. chrysopygus, among the genus Leoll/opilhecus, has adapted to areas with strong seasonality ofclimate and resourc es.